ANALISIS PESAN PADA FILM “DUA GARIS BIRU” - Hamim 45 (Sintesa, 2023)
"Dua Garis Biru" is a romantic drama film directed by Ginatri S. Noer, which was released in Indonesian cinemas in 2019. It tells the story of a high school couple who engage in premarital sex and face an unintended pregnancy, highlighting the importance of parental involvement and the surrounding environment in the development of their child. The film portrays a common phenomenon in Indonesia, namely early marriage and teenage pregnancy. "Dua Garis Biru" received 11 awards in 2019 and 2020, including the Piala Maya for Best Feature Film or Selected Cinema Film. This research aims to analyze the moral messages regarding early marriage present in "Dua Garis Biru." The study will observe the explicit and implicit moral messages conveyed by the film, focusing on the concepts of moral messages by Nurgiyantoro and utilizing Gillian Rose's visual analysis from three research areas: the site of self, the site of audience, and the site of production. The research methodology employed is qualitative. The findings of the study indicate that "Dua Garis Biru" contains moral messages regarding the relationship between humans and God, the relationship between humans and themselves, and the relationship between humans and others.